KESADARAN ATAS REALIT AS: KAJIAN SVAMI CHINMA YANANDA TERHADAP MANDUKYA UPANISAD - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Knowledge and technology development has given a lot of advantages in the human life. In the other side, bad effects of this development also cause ignorance of spiritual life. The life has only meaning in material relation (in the extensive meaning)